(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aims to analyze the implementation of Science and Engineering Practices (SEP) in physics practicum activities, focusing on three main aspects: readiness, implementation, and student results. This study used a quantitative descriptive approach through structured observation data collection of Physics classes. The aspects assessed included the readiness of practicum equipment and materials, the effectiveness of the division of tasks in the group, the active involvement of students, the application of the Project Based Learning (PjBL) method, and the ability of students to apply SEP, including experimental design, data collection and analysis, physics model making, and preparation of practicum report results. The results showed that implementing the physics practicum in the Good category had an average score of 76.2. The application of SEP, especially in the use of technology and the ability to work together, also contributed significantly to the effectiveness of the practicum. This finding confirms the importance of strengthening science and engineering practices in physics practicum learning and its implications for the development of students’ scientific and technical skills.